Hydraulic Transport of Sand and Lime Slurries in a Vertical Pipeline - Joel, Brian L. (My University, 1980)
This thesis is primarily concerned with the energy required to hydraulically transport sand and lime slurries in a 5.1 cm.-diameter vertical pipeline for both steady and pulsating flows.
In the steady flow experiments, three different grades of sand of average weighted diameter d = 0.66, 1.20 and 1.84 mm. were investigated. The lime flurry used had an average particle diameter of 1.8 x 10⁻³ mm. The delivered volumetric concentration C₅, the average mixture flow rate Q, and the pressure difference ΔP across the test section were measured within the Reynolds number range of 4 x 10⁴ to 2 x 10⁵.
In the pulsating flow experiments, only one grade of sand of average weighted diameter d = 1.20 mm. was investigated at frequencies of 0.22 and 0.44 cycles per second.
Two methods of predicting pressure gradient for slurry flow were attempted. The first was adapted from Newitt et. al. (1961). By comparing the measured pressure gradient i for various suspensions to those for water flowing under similar conditions iw, an excess dimensionless pressure parameter Φ was obtained. It was possible to correlate the steady flow data using Φ and another dimensionless parameter Ψ related to mixture velocity Vm, diameter ratio D/d and specific gravity of solid S. In the second method the excess pressure gradient (i-iw) is equated to the excess hydraulic head CT(S-1). The results are presented in graphical form and each method is appraised in the discussion.
The energy dissipated per unit height of the test section and mass flow rate was determined for steady and pulsating flow of suspensions. The energy ratio JP/Js at the two frequencies was obtained for low concentration slurries (Cs < 8.0%). It was found that no energy savings were recorded for pulsatile flow under these conditions.
Keywords: Mechanical Engineering; Mechanical Engineering